2008
DOI: 10.1189/jlb.1207832
|View full text |Cite
|
Sign up to set email alerts
|

Priming of neutrophil oxidative burst in diabetes requires preassembly of the NADPH oxidase

Abstract: Hyperglycemia associated with diabetes mellitus results in the priming of neutrophils leading to oxidative stress that is, in part, responsible for diabetic complications. p47phox, a NADPH oxidase cytosolic subunit, is a key protein in the assembly of the NADPH oxidase leading to superoxide generation. Little is known about the priming mechanism of oxidative pathways in neutrophils of people with diabetes. In this study, the kinetics of p47phox activation was investigated by comparing neutrophils from diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 69 publications
4
91
0
3
Order By: Relevance
“…Phox translocation to the membrane in neutrophil-like HL-60 cells (Omori et al, 2008). The uncoupling of nitric oxide synthase (NOS) has also been described in diabetic rats, directly relating it to ROS production (Koo and Vaziri, 2003).…”
Section: Role Of Reactive Oxygen Species In Diabetes Sources Of Reactmentioning
confidence: 99%
“…Phox translocation to the membrane in neutrophil-like HL-60 cells (Omori et al, 2008). The uncoupling of nitric oxide synthase (NOS) has also been described in diabetic rats, directly relating it to ROS production (Koo and Vaziri, 2003).…”
Section: Role Of Reactive Oxygen Species In Diabetes Sources Of Reactmentioning
confidence: 99%
“…Taken together, our study shows that neutrophils in T2D produce excess levels of IL-6 and may be responsible for inducing a constitutively active state. Omori et al (2008) demonstrated that high glucose induces ERK1/2 mediated premature translocation of p47 phox subunit of NADPH oxidase to cell membrane in diabetic neutrophils leading to constitutive generation of superoxides [19]. Clinical and experimental data strongly suggests that NADPH oxidase derived oxygen free radicals are the key components required for NETosis.…”
Section: Pro-inflammatory Conditions During Hyperglycemia Favor Constmentioning
confidence: 99%
“…There has already been evidence that glucose can alter blood ROS generation [12][13][14][15][16][17][18][19]: 11 mM glucose reduced the neutrophils' respiratory burst by 28% ± 5% and 56 mM glucose by 74% ± 7% [12]. 50% decreased ROS generation was detected at 25 mM glucose [13].…”
Section: Discussionmentioning
confidence: 99%